Ain't Misbehavin: Discussion of "Somatic Experiencing". Issue 5 (3rd September 2018) - Bass, Graham
Abstract : A consideration of David Levit's (this issue) paper "Somatic Experiencing: In the Realms of Trauma and Dissociation …" from a perspective of multiple self states and the enacted dimension.